Enhancing ESL learners' English pronunciation via phonetic alphabet training / Wan Nurul Aini Wan Shuib - Wan Shuib, Wan Nurul Aini (2014)
The purpose of this study is to identify the pronunciation problems faced by ESL learners and to investigate the effect of phonetic alphabet training on ESL learners’ pronunciation of English words. This study constitutes a pre-test, an intervention (phonetic alphabet training), and a post-test. At the pre-test, the participants were given a test to diagnose their pronunciation problems. At the intervention, the participants who have never received any instruction on phonetic alphabets were given phonetic alphabet training for nine weeks which emphasized on the drilling of the production of vowel and consonant sounds. After nine weeks, the participants were given a post-test to identify the effectiveness of the phonetic alphabet training. This study discovered that ESL learners had problems pronouncing vowel sounds and the phonetic alphabet training did not wholly positively enhance ESL learners’ English pronunciation. This seems to confirm Lenneberg’s (1967) theory that the stage before puberty is more successful for language learning. This study should raise the awareness of the importance of equipping ESL learners with phonetic alphabet training at the young age. This is because ‘age’ influences the acquisition of a second language and will impede learners’ success of acquiring phonetic alphabet knowledge when they learn it as adults. It is hoped that this study serves as a template for further research on phonetic alphabet training and persuade curriculum developers to include phonetic alphabet training in the school’s curriculum.